Dangers for Ireland of an EMU without the UK: some calibration results - Barry, Frank (Economic & Social Studies, 1997)
This paper presents a small-open-economy model calibrated to Irish data. The model can be used for many purposes. It is applied here to the EMU debate. It comes close to replicating the employment effects of sterling weakness (with Ireland in EMU) reported in the recent ESRI study (Policy Research Series Paper No. 28, 1996). When the assumptions on wage flexibility are changed in an arguably more plausible direction, though, we find that the employment effects are magnified considerably. Given the narrowness of the outcome in the ESRI's judgement, our results provide support to remaining outside EMU until the UK joins.
Keywords: European Monetary Union; Sterling; Ireland; Irish economy